Violence and Burnout in Health Care Emergency Workers in Santiago, Chile: A Survey-Based Cross-Sectional Study - Bachelet-Norelli, V (Elsevier Ltd, 2019)
Shortage of quantitative studies regarding health risks for emergency services workers is a concern for Chilean s occupational health organizations. Objective: To explore the incidence of violence and burnout in emergency services of the Metropolitan Region of Chile, and associations with workers’ characteristics and workplace conditions. Methods: A cross-sectional study was carried out from January to August 2016. A self-reported questionnaire explored about frequency and seriousness of violence episodes and about symptoms of burnout with the Maslach Burnout Inventory. Results: Of the 565 workers participating, 71% (95% CI 66.7–74.5) said violence episodes occurred at least once a week; 71.3% (95% CI 67.3–75.0) were victims of some aggression in the previous 12 months. Patients companions, relatives or friends arose as the main aggressors and the severity of the episodes was considered slight or moderate by more than 50% of participants. Fifty-seven respondents (10.5%, CI 95% 8.1–13.5) classified as having a burnout syndrome. Having been a victim of violence was associated to high emotional exhaustion (ORadj = 1.7, 95% CI: 1.1–2.8) and depersonalization (ORadj = 2.0, 95% CI 1.3–3.3). Conclusions: Violence is a problem in the emergency departments of Chile s Metropolitan Region. Burnout is also present and independently associated to violence. © 2019 Elsevier Ltd